Chemical Composition Analysis of TiAlBN Nanocomposite Coating Deposited via RF Magnetron Sputtering - Mohd Rosli, ZULKIFLI; Mahamud, zainab; Wai Loon, Kwan; Jariah, Mohamad Juoi; Lau, K.T. (2014)
TiAlBN nanocomposite coating have been successfully deposited on AISI 316 substrate via RF magnetron sputtering by varying nitrogen-to-total flow ratio (RN) of 5, 15, 20, 25%, as well as varying substrate temperature of 100, 200, 300, and 400 ºC; using single Ti-Al-BN hot-pressed target. Chemical compositions of the coatings were analysed using X-ray photoelectron spectroscopy (XPS). XPS results showed that the TiAlBN nanocomposite coating reaches a nitride saturated state at higher RN (e.g 15, 20, and 25%) and boron concentration was found to be approximately 9 at.%. However, as the concentration of nitrogen decreases at lower RN (5%), boron concentration was found to increase to 16.17 at. %. This is due to the increase of TiB2 phase in the coating. Variations of substrate temperatures were found to give no significant effect on the chemical composition of the deposited TiAlBN nanocomposite coating.